Dual-pathway tumor radiosensitization strategy based on engineered bacteria capable of targeted delivery of AuNPs and specific hypoxia alleviation - Lingling Lei; Haonan Xu; Mingjie Li; Meng Du; Zhiyi Chen (Journal of Nanobiotechnology)
Abstract Background Radiotherapy efficacy remains constrained by two key challenges: dose-dependent toxicity to healthy tissues at high radiation doses and hypoxia-mediated tumor radioresistance. While radiosensitizers like gold nanoparticles can enhance tumor-specific radiation deposition, their targeted delivery to tumors presents a significant hurdle. Bacteria have emerged as promising bio-carriers that not only actively target tumors and penetrate complex microenvironments, but can also be genetically engineered as multifunctional platforms for radiosensitizer delivery and hypoxia alleviation. Results An integrated nanosystem (PCM@AuNPs), composed of engineered bacteria (PCM) and gold nanoparticles (AuNPs), is used to increase the effectiveness of radiotherapy. PCM can target and colonize tumor sites more effectively, thus improving the delivery efficiency of radiosensitizers. Furthermore, PCM overexpresses catalase (CAT), which decomposes excess H2O2 into O2, helping to mitigate hypoxia in the TME. Under X-ray irradiation, PCM@AuNPs significantly enhance radiosensitization, leading to improved tumor growth inhibition while maintaining good biocompatibility. Conclusions An effective strategy based on an integrated nanosystem (PCM@AuNPs) for radiosensitization through multiple pathways is developed. This novel engineered bacterial strategy holds great promise for enhancing radiosensitization in cancer therapy.